A comparative study of individualized and group-based instruction in mandarin learning for beginner students - Ivana Ivana (Jurnal Konseling dan Pendidikan, 2025)
Beginner learners of Mandarin often struggle with pronunciation, pinyin, and complex vocabulary, especially when instructional materials are not adapted to their proficiency levels. This study aims to compare the effectiveness of individualized instruction (one-to-one tutoring) and group-based instruction (one-to-many teaching) in supporting beginner students’ Mandarin learning. Using a descriptive qualitative approach with a case study design, the research involved 35 middle school students at Charles Wesley Methodist Private Middle School. Five students with the lowest pretest scores received one-to-one instruction, while the remaining thirty participated in group-based learning. Data were collected through participatory observation, documentation of learning outcomes, and student reflections, and analyzed using Miles and Huberman’s framework, including reduction, categorization, and thematic analysis. Results show that one-to-one instruction was particularly effective in improving pronunciation accuracy and comprehension for low-achieving and less confident students, while group-based instruction fostered motivation, peer collaboration, and vocabulary mastery, especially among active learners. The findings emphasize that teaching effectiveness depends on aligning instructional methods with learner characteristics. This study contributes to second language acquisition research by highlighting the importance of differentiated instruction. Limitations include the small sample size, single-site context, and the dual role of the researcher. Future research should expand the participant pool and explore hybrid models combining the strengths of both approaches.